Dispatch of a helicopter emergency medicine service to patients with a sudden, unexplained loss of consciousness of medical origin - Mohindru, J. (BMC Emerg Med, 2020)
BACKGROUND: Sudden loss of consciousness (LOC) in the prehospital setting in the absence of cardiac arrest and seizure activity may be a challenge from a dispatcher’s perspective: The aetiology is varied, with many causes being transient and mostly self-limiting, whereas other causes are potentially life threatening. In this study we aim to evaluate the dispatch of HEMS to patients with LOC of medical origin, by exploring to which patients with a LOC HEMS is dispatched, which interventions HEMS teams perform in these patients, and whether HEMS interventions can be predicted by patient characteristics. METHODS: We performed retrospective cohort study of all patients with a reported unexplained LOC (e.g. not attributable to a circulatory arrest or seizures) attended by the Air Ambulance Kent, Surrey & Sussex (AAKSS), over a 4-year period (July 2013–December 2017). Primary outcome was defined as the number of HEMS-specific interventions performed in patients with unexplained LOC. Secondary outcome was the relation of clinical- and dispatch criteria with HEMS interventions being performed. RESULTS: During the study period, 127 patients with unexplained LOC were attended by HEMS. HEMS was dispatched directly to 25.2% of the patients, but mostly (74.8%) on request of the ground ambulance crews. HEMS interventions were performed in 65% of the patients (Prehospital Emergency Anaesthesia 56%, hyperosmolar therapy 21%, antibiotic/antiviral therapy 8%, vasopressor therapy 6%) and HEMS conveyed most patients (77%) to hospital. Acute neurological pathology was a prevalent underlying cause of unexplained LOC: 38% had gross pathology on their CT-scan upon arrival in hospital. Both GCS (r = − 0.60, p < .001) and SBP (r = 0.31, p < .001) were related to HEMS interventions being performed on scene. A GCS < 13 predicted the need for HEMS interventions in our population with a sensitivity of 94.9% and a specificity 75% (AUC 0.85). CONCLUSION: HEMS dispatchers and ambulance personnel are able to identify a cohort of patients with unexplained LOC of medical origin who suffer from potentially life threatening (mainly neurological) pathology, in whom HEMS specific intervention are frequently required. Presenting GCS can be used to inform the triage process of patients with LOC at an early stage. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12873-020-00388-x.